The Effect Of Dismenorea Concerning The Reduction Of Primary And Secondary Menstrual Pain Intensity On Adolescents In Sma Trisakti Medan North Sumatera - Simbolon, Marlina; Kristina, Ingka; Asnita; Simbolon, Hertanta; Nduma, Sari (Mitra Husada Health Internasional Conference (MIHHICo), 2020)
Menstruation is a natural and natural process in a woman's life. Dysmenorrhoea is pain in the abdomen that comes from cramping of the uterine muscles and occurs during menstruation without signs of pelvic infection or disease. The intensity of dysminorrhea can decrease after pregnancy or at the age of about 30 years. The research design used a quasi-experimental method (Quasi Experiment) with a one group pre-post test design. This research was conducted at SMA TRISAKTI Medan, North Sumatra Province from April to October 2020. The population in this study were 311 female adolescent students and 113 students as samples. in accordance with the research flow diagram that has been determined from planning to the outcome. The sample in this study were 113 adolescents at TRISAKTI Medan Senior High School, North Sumatra Province using the Simple Random Sampling Technique for adolescents with dysmenorrhea. The results of univariate data show that the majority of female teenage students in class XII are 108 students (34.7) and a minority in class X are 100 (33%) and the majority of respondents are moderate pain as many as 53 students (46.9) and a minority of severe pain as much as 22 (19.5%). The results of the bivariate test used the Wilxocon test to determine the average difference between menstrual pain and the value (p-value = 0,000), namely that there was an effect of dysmenorrhoea exercise on decreasing menstrual pain intensity, there were teenage girls in SMA TRISAKTI Medan. Dysmenorrhoea exercise is a complementary therapy that can be used by health facilities and the community to reduce menstrual pain and reduce the use of pain relievers.